2001
DOI: 10.1182/blood.v97.8.2381
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I inhibits the production of interleukin-1β and tumor necrosis factor-α by blocking contact-mediated activation of monocytes by T lymphocytes

Abstract: Tumor necrosis factor-␣ (TNF-␣) and interleukin-1␤ (IL-1␤), essential components in the pathogenesis of immunoinflammatory diseases, are strongly induced in monocytes by direct contact with stimulated T lymphocytes. This study demonstrates that adult human serum (HS) but not fetal calf or cord blood serum displays inhibitory activity toward the contact-mediated activation of monocytes by stimulated T cells, decreasing the production of both TNF-␣ and IL-1␤. Fractionation of HS and N-terminal microsequencing as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
243
0
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(277 citation statements)
references
References 58 publications
13
243
0
11
Order By: Relevance
“…As response to stressors (including arterial wall damage) IL-1β and TNF-α stimulate the production of IL-6 which activates the APR. It has been demonstrated that Apo A-I, the principal apoprotein of HDL particles, has a strong anti-inflammatory activity by specifically blocking the contact-mediated activation of monocytes by stimulated T cells, thus inhibiting IL-1β and TNF-α production [33]. In the presence of low HDL-C, and consequently of apo A-I levels, this inhibitory mechanism would be impaired, and the activation of the inflammatory cascade would be easier.…”
Section: Discussionmentioning
confidence: 99%
“…As response to stressors (including arterial wall damage) IL-1β and TNF-α stimulate the production of IL-6 which activates the APR. It has been demonstrated that Apo A-I, the principal apoprotein of HDL particles, has a strong anti-inflammatory activity by specifically blocking the contact-mediated activation of monocytes by stimulated T cells, thus inhibiting IL-1β and TNF-α production [33]. In the presence of low HDL-C, and consequently of apo A-I levels, this inhibitory mechanism would be impaired, and the activation of the inflammatory cascade would be easier.…”
Section: Discussionmentioning
confidence: 99%
“…HDL is considered a negative acute-phase protein (Malle et al, 1993) and has been found to be negatively associated to C-reactive protein (CRP) and acute and Glycemic index in chronic disease LS Augustin et al chronic inflammatory states (Bausserman et al, 1988;Rossner, 1978;Hardardottir et al, 1994). HDL may reduce the inflammatory response by binding to stimulated T cells thus blocking their interaction with monocytes and consequently inhibiting TNF-a and IL-1b (Hyka et al, 2001). A possible mechanism could therefore be that lower glucose raises after low-GI foods may reduce the inflammatory response and raise HDL levels, when compared to high-GI foods.…”
Section: The Glycemic Index In Coronary Heart Diseasementioning
confidence: 99%
“…Moreover, the composition of the HDL is altered during inflammation: the huge increase in serum amyloid A induces the displacement of the apolipoprotein A-1 particle, which contains the antioxidant enzyme paraoxonase-1 (PON-1), from HDLs, thus reducing the HDL anti-inflammatory properties (Hyka et al, 2001). PON-1 is an anti-oxidative enzyme and a negative acute phase reactant that is related with HDL, and decreases in serum due to both a reduced production and to an increased peripheral consumption associated with oxidation (Feingold et al, 1998).…”
Section: Introductionmentioning
confidence: 99%